Practical active control of cavity noise using loop shaping: Two case studies - Kim, Sang-Myeong [UNESP]; Pereira, Joao A. [UNESP]; Lopes, Vicente [UNESP]; Turra, Antonio E. [UNESP]; Brennan, Michael J. [UNESP] (Elsevier, 2017)
A simple loop shaping technique is applied to design an optimal, robust feedback controller to reduce the interior noise of an acoustic cavity. It is a data-based technique that uses the measured plant response to tune the parameters of a fixed-structure controller in a graphical way. The two cases studied are narrowband noise control in a small cavity and broadband noise control in a long duct. Each control system consists of a microphone, a loudspeaker, and a controller connecting the two transducers that are further collocated. The fixed-structure of each controller should be chosen ahead of loop shaping and is determined in this paper solely based on the Nyquist plot of each plant measured. It turns out that a single band (high) pass filter of second order is suitable for the narrowband (broadband) noise control case considered. It is finally demonstrated with experiments that the technique is practical and a second order filter can be effectively used for active control of cavity noise in a single narrow or broad frequency band.
Keywords: Loop shaping; Noise control; Robust control; Second order filters, optimal control